The level of mindfulness in interpersonal relationships - the validity and reliability of the assessment scale - Dučić, Bojan; Kaljača, Svetlana (Specijalna edukacija i rehabilitacija, 2023)
Introduction. The multidimensional concept of mindfulness includes voluntary attention, focus on the "present moment", monitoring of mental processes, and inhibition of impulsive reactions. Examining the impact of the level of mindfulness on the quality of the relationship between the special educator and the student requires an instrument with satisfactory psychometric characteristics. Objectives. The goal of this research was to determine the internal consistency, test-retest reliability, convergent and discriminative validity of the Interpersonal mindfulness scale. Methods. The reliability of the Interpersonal mindfulness scale was checked by calculating Cronbach’s alpha in a sample of 114 students (age: M = 20.75, SD = 2.20). For the test-retest reliability check, a sample of 32 students was formed (age: M = 21.41, SD = 2.46). The relationship between the Interpersonal mindfulness scale and the Cognitive and affective mindfulness scale was determined in a sample of 59 students (age: M = 20.93, SD = 1.92). For examining the Pearson correlations of the Interpersonal mindfulness scale and the Perceived Stress Scale–10, the sample included 55 students (age: M = 20.55, SD = 2.47). Results. It was determined that the values ​​of the internal consistency of the Interpersonal mindfulness scale and its subscales were acceptable (α = .69 – .88), the level of test-retest reliability was moderate to high (ICC = .58 –.91), the correlation with the overall results of the Cognitive and affective mindfulness scale was statistically significant and positive (r = .58, p < .001), while it was not statistically significant (p > .05) on the Perceived Stress Scale–10. Conclusion. Based on the established reliability and validity, the Interpersonal mindfulness scale can be recommended as an instrument for obtaining reliable data on the quality and level of mindfulness manifested in social interactions.
Keywords: mindfulness; interpersonal relations; validity; reliability